2012
DOI: 10.7324/japs.2012.2611
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sub-chronic chlorpyrifos poisoningon immunological and biochemical changes in ratsand protective effect of eugenol

Abstract: Chlorpyrifos (CPF) is one of the most widely used organophosphorus (OP) insecticides until 2000 when the United States Environmental Protection Agency restricted some of its domestic uses due to its toxicity. Despite this, CPF remains one of the most widely used OP insecticides. Eugenol is a flavoring agent used in cosmetic and food products. Furthermore, eugenol acts as a pro-oxidant and as an anti-oxidant, under certain circumstances. Therefore, the present study aims to evaluate the possible immuno-toxicogi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…A previous report has indicated that CP has effects on mortality of the cells such as neurons[ 39 ] by different mechanisms such as cell signaling and starting cascades, and also changing gene transcription factors, which are activated by reactive oxygen species (ROS). [ 40 ] Toxic effect of CP is supported by results of flow cytometry in the present study. As shown in the Figure 4 , in the control group, which was not exhibited to any dose of MgO NPs, lymphocytes were distributed mostly in quarter C (83%) and the rate of apoptotic and necrotic cells was really depressed.…”
Section: Discussionsupporting
confidence: 82%
“…A previous report has indicated that CP has effects on mortality of the cells such as neurons[ 39 ] by different mechanisms such as cell signaling and starting cascades, and also changing gene transcription factors, which are activated by reactive oxygen species (ROS). [ 40 ] Toxic effect of CP is supported by results of flow cytometry in the present study. As shown in the Figure 4 , in the control group, which was not exhibited to any dose of MgO NPs, lymphocytes were distributed mostly in quarter C (83%) and the rate of apoptotic and necrotic cells was really depressed.…”
Section: Discussionsupporting
confidence: 82%
“…A similar decrease in leukocyte counts was observed in rodents intoxicated with other organophosphates, such as chlorpyrifos and monocrotophos (Janardhan & Sisodia, 1990;Elelaimy et al, 2012). Also, exposure to glyphosate (Roundup ® ) -an OP herbicide, induced a decrease in total leukocyte counts in newborn broad snouted caiman (Caiman latirostris) (Siroski et al, 2016).…”
Section: Discussionsupporting
confidence: 51%
“…At the end of the designed period (20 days), Blood samples were collected for haematological analysis. Analysis was based on the method designed by Elelaimy et al (2012). Mean cell haemoglobin (MCH), mean cell volume (MCV) and mean cell haemoglobin concentration (MCHC) were calculated respectively using standard formular described by Dacie and Lewis (1991).…”
Section: General Bioassay Techniquementioning
confidence: 99%